2002
DOI: 10.3346/jkms.2002.17.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Purulent Pericarditis Caused by Group G Streptococcus as an Initial Presentation of Colon Cancer

Abstract: Bacterial pericarditis has been recognized as a rare disease since the development of antibiotics. Usually, the disease is associated with underlying conditions or a seeding of infection elsewhere to the pericardium. Here we describe a case of group G streptococcal pericarditis as an initial presentation of colon cancer. A 52-yr-old man was admitted because of dyspnea. An electrocardiogram showed a diffuse ST-segment elevation and a two-dimensional echocardiogram showed a large amount of pericardial effusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…Several species of bacteria have been linked to chronic infections of the colon and increased risk of colon cancer including Escherichia coli [ 46 ] and several streptococci [ 47 , 48 ]. Recent studies, however, have validated earlier findings of an association between colon cancer and Streptococcus bovis [ 11 , 12 ].…”
Section: Bacteria and Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of bacteria have been linked to chronic infections of the colon and increased risk of colon cancer including Escherichia coli [ 46 ] and several streptococci [ 47 , 48 ]. Recent studies, however, have validated earlier findings of an association between colon cancer and Streptococcus bovis [ 11 , 12 ].…”
Section: Bacteria and Carcinogenesismentioning
confidence: 99%
“…Evidence has shown that over-expression of COX-2 has a major role in mucosal inflammation [ 47 ] and is associated with inhibition of apoptosis [ 54 ] and enhancement of angiogenesis [ 55 ], which favor cancer initiation and development. It was reported by Biarc et al [ 11 ] that S. bovis proteins also promoted cell proliferation by triggering mitogen-activated protein kinases (MAPKs), which can increase the incidence of cell transformation, the rate of genetic mutations and up-regulate COX-2.…”
Section: Bacteria and Carcinogenesismentioning
confidence: 99%
“…Anaerobic infection of the pericardium can result from (1) a spread from a contiguous focus of infection, either de novo or after surgery or trauma (pleuropulmonary, esophageal fistula or perforation, and odontogenic); (2) a spread from a focus of infection within the heart, most commonly from endocarditis; (3) a hematogenous infection, and (4) a direct inoculation as a result of a penetrating injury or cardiothoracic surgery [95,96].…”
Section: Bacteriology Of Pericardial Effusionmentioning
confidence: 99%
“…[25,26], Escherichia coli [27] eta Streptoccocus spp. [28,29]. Bakterio horiek erabilitako mekanismoak oso ezagunak izan ez arren, Streptococcus bovis bakterioaren kasuan bere paretako proteinak koloneko minbiziaren garapena azkartzeko gai direla frogatuta dago [30].…”
Section: Bakterioakunclassified